New Architectural Viewpoint for Enhancing Society’s Resilience for Multiple Risks Including Emerging COVID-19 - Takewaki, Izuru (Frontiers in Built Environment, 2020)
The spread of COVID-19 all over the world since the beginning of the year 2020 requires a re-thinking of the meaning of the term “resilience” in the field of architecture and architectural engineering. Resilience from the viewpoint of architecture and architectural engineering has been investigated primarily in terms of conventional natural disaster risks (see, for example, Bruneau et al. 2003, Cimellaro et al. 2010, AIJ 2020a). However, COVID-19 reminds us of the need to investigate resilience also in terms of infection risks. The places where people become infected are principally within buildings and transportation systems. Especially in buildings, three factors considered to be main risks for infection (closed spaces without ventilation, dense gatherings, close connection) often occur. For this reason, the role of architecture and architectural engineering is essential from the viewpoint of reducing the risk of infection, using versatile knowledge and technologies from the fields of architectural and regional planning. Following the appearance of COVID-19, architectural designers and engineers have an important mandate to think about the role of buildings and their related fields.